2007
DOI: 10.1507/endocrj.k07-040
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Magnesium Deficiency Associated with Insufficient Parathyroid Hormone Action and Severe Osteoporosis

Abstract: Abstract. The relationship between osteoporosis and magnesium (Mg) deficiency is still controversial. Here we report a case of an 82-year-old woman with a giant adenomatous goiter and severe osteoporosis with multiple vertebral fractures, whose clinical course indicated that her osteoporosis was probably due to Mg deficiency. She visited our hospital for treatments of tetany. Laboratory data showed the existence of hypomagnesemia, hypocalcemia, hypokalemia, vitamin D deficiency, and slightly elevated intact PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…These data suggest that a blunted PTH response in hypo-Mg patients may be the causative factor for BMD reduction in SCD. These results are supported by previous studies which suggested that Mg deficiency causes impairment of PTH release from the parathyroid and the refractoriness of bone and kidney to the hormone, which may lead to the suppression of bone remodelling [14, 25, 31, 32]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data suggest that a blunted PTH response in hypo-Mg patients may be the causative factor for BMD reduction in SCD. These results are supported by previous studies which suggested that Mg deficiency causes impairment of PTH release from the parathyroid and the refractoriness of bone and kidney to the hormone, which may lead to the suppression of bone remodelling [14, 25, 31, 32]. …”
Section: Discussionsupporting
confidence: 88%
“…Additionally, Mg regulates biological processes important in bone remodelling such as calcium absorption, parathyroid hormone (PTH) secretion, osteoblast adhesion and bone formation [11–13]. The Mg deficiency produces hormonal and skeletal disturbances that have been associated with a number of bone disorders including osteoporosis [14, 15]. This has been supported by experimental magnesium deficiency studies showing that insufficient dietary Mg intake increased osteoclast number, and bone loss in laboratory animals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporotic postmenopausal women with a positive magnesium-loading test for magnesium deficiency were vitamin D deficient and had low serum parathyroid hormone levels (112,117). In another study, osteoporosis was reversed by oral magnesium treatment, with subsequent improvement in bone mineral density (50).…”
Section: Osteoporosis and Agingmentioning
confidence: 99%
“…Patients with hypomagnesemia are at risk for bone fractures along with osteoporosis (50,109). Hypomagnesemia is often associated with other diseases that occur in elderly patients where a reduction in bone mass is associated with a reduction of magnesium content (7,118).…”
Section: Osteoporosis and Agingmentioning
confidence: 99%
“…Magnesium deficiencies lead to reduced levels of 1,25(OH) 2 D 3 vitamin in serum, slightly elevated intact parathormone and increased osteoclast activity. The number of osteoblasts decreases [ 27 ]. Malfunction of bone mineralization is similar to osteomalacia.…”
Section: Magnesiummentioning
confidence: 99%